Describing LSIC Indigenous communities: Some preliminary exploration of data quality of community variables in LSIC data - MacKay, M; Hunter, B (My University, 2011)
LSIC provides a potentially useful source of information on Indigenous children, but it is important that users understand some basic aspects of the survey design and data quality. This paper attempts to provide some useful background by identifying some of the geographical nuances of the LSIC data with an initial focus on how study communities differ from other similar communities. The analysis makes extensive use of information on Indigenous areas from the 2006 census to describe LSIC communities, but also tests the internal consistency of the data with a local geographic dimension in the first wave of the study. The Intra-Correlation Coefficient (ICC) will be used to document the correlation of response for 'community' LSIC variables within Indigenous Area geography. ICCs can be estimated for data derived from the following questions: Is this a good community or neighbourhood for little kids?; Are there good places for kids to play in this community or neighbourhood?; Is this a noisy neighbourhood?; and finally How safe would you say this community or neighbourhood is? This will not be perfect validation of the data but will allow the user to be more confident that the data is reasonably consistent with the local geography. Some preliminary exploration of the association between community level data from the census and LSIC and some rudimentary child outcomes will be attempted.
Keywords: Social Capital -- Communities and Neighbourhoods; Social engagement; Social Capital; Communities and Neighbourhoods; Social Engagement